(untitled) (Applied Biological Research, 2022)
Washingtonia filifera has many health benefits, but its activity against cancer cell lines has not yet been explored. The present study assessed the cytotoxicity of different solvent extracts of W. filifera using MTT assay. Fluorescence microscopy was used to evaluate apoptosis and oxidative stress. Only two extracts showed dose- and time-dependent decrease in cell survival. The ethyl acetate extract of W. filifera (WFET) exhibited maximum cytotoxicity against HUVECs, MCF7, HCT116, and HepG2 cells with IC50 values of 21.7, 48.8, 85.8, and 100.6 µg mL-1, respectively, 24 h post-treatment. Similarly, methanolic extract of W. filifera (WFME) showed maximum cytotoxicity against HUVECs (IC50: 21.8 µg mL-1) cells, followed by MCF-7 (73.3 µg mL-1), HCT116 (98.5 µg mL-1), and HepG2 (100 µg mL-1). Light and florescent microscopy using 4′,6- diamidino-2-phenylindole, and acridine orange-ethidium bromide dyes showed apoptotic cell death. Intracellular reactive oxygen species (ROS) was evaluated using DCFH-DA dye. The WFET and WFME extracts showed increased intracellular ROS with increased concentrations of the two extracts using MCF7 cells. Overall, the WFME and WFET extracts could hemo-preventive agents against breast carcinoma cells.